Q: What is x in -83 equals 9x-2?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

9x2-9x = 0 x2-x = 0 x(x-1) = 0 x = 1 or x = 0

27.67 x 3 = ~83

I x=5 and y=2, then (5x5)=25 plus (9x2)=18. 25+18=43

9x-53=6/x 9x2-53x=6 9x2-53x-6=0 9x2+x-54x-6=0 x(9x+1)-6(9x+1)=0 (9x+1)x(x-6)=0 9x+1=0 or x-6=0 9x=-1 or x=6 x=-1/9 or x=6

1 times 249, for starters. also 3 times 83

Related questions

9x2-9x = 0 x2-x = 0 x(x-1) = 0 x = 1 or x = 0

x = 4

9x2 + 7x = 2 9x2 + 7x - 2 = 0 9x2 + 9x - 2x - 2 = 0 9x(x + 1) - 2(x + 1) = 0 (9x - 2)(x + 1) = 0 x ∈ {-1, 2/9}

9x2+6x-7 = 0 Using the quadratic equation formula:- x = 0.6094757082 or x = -1.276142375

x=5

83 x 1

9x2 + 3x / 3x equals (3x + 1).9x2 + 3x divided by x is 9x + 3 , and then divided by 3 yields the 3x +1.

1 x 83.

3 x 6 = 18

27.67 x 3 = ~83

I x=5 and y=2, then (5x5)=25 plus (9x2)=18. 25+18=43

9x2 = 2x Get the 2x to the left side to get 9x2 - 2x = 0 Use cuadratic formula to solve for x knowing that c is 0 x = [ -b +- sqrt (b2-4ac) ]/2a